2016
DOI: 10.3892/ol.2016.4985
|View full text |Cite
|
Sign up to set email alerts
|

Comparable roles of CD44v8-10 and CD44s in the development of bone metastases in a mouse model

Abstract: Abstract. Cluster of differentiation (CD)44 has been implicated in cancer metastasis to bone. Clinical and experimental studies have suggested that the standard isoform of CD44 (CD44s) and the variant isoform of CD44 (CD44v) enhance metastasis. The present study examined the differential roles of CD44s and CD44v, particularly CD44v8-10, in the development of bone metastases. For this purpose, MDA-MB-231 human breast cancer cells and A549 human lung cancer cells were stably transduced with epithelial splicing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Conversely, we observed that CM derived from CD44v8-10 pos cells reduced osteoblast ALP staining, intriguingly suggesting that these tumor cells are able to take control of bone microenvironment impairing the normal bone remodeling process. In the literature, the role of this CD44 variant in the onset of metastasis is unclear because it has been shown that CD44 expression promotes bone metastases in human breast cancer 63 and that CD44v8-10 and CD44s possess comparable roles in the development of bone metastases in a mouse model of breast cancer 64 . Therefore, to determine whether osteomimetic traits displayed by CD44v8-10 pos PC cells were dependent on CD44v8-10 expression, we evaluated the expression of osteomimetic genes in cells knocked down for CD44v8-10 by siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we observed that CM derived from CD44v8-10 pos cells reduced osteoblast ALP staining, intriguingly suggesting that these tumor cells are able to take control of bone microenvironment impairing the normal bone remodeling process. In the literature, the role of this CD44 variant in the onset of metastasis is unclear because it has been shown that CD44 expression promotes bone metastases in human breast cancer 63 and that CD44v8-10 and CD44s possess comparable roles in the development of bone metastases in a mouse model of breast cancer 64 . Therefore, to determine whether osteomimetic traits displayed by CD44v8-10 pos PC cells were dependent on CD44v8-10 expression, we evaluated the expression of osteomimetic genes in cells knocked down for CD44v8-10 by siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…CD44v8-10, also known as CD44R1 and CD44E, is one of the isoforms of CD44v and contains variant exons 13-15 (v8-v10) (Ponta et al, 2003;Zöller, 2011). Clinical studies have shown that CD44v8-10 is 1 (Phase 3) SCLC immunotherapy 42 (34 studies for phase 1, 2; 4 studies for phase 3; no studies for: phase 4) Small cell lung cancer CART 1 (Phase 1) Small cell lung cancer CART Mesothelin 0 Cancer stem cells small cell lung cancer CART cell immunotherapy 0 expressed on a variety of human epithelial malignant tumors, including lung tumors and CSC, and its expression correlates with metastasis (Yamaguchi et al, 1995;Yamaguchi et al, 1996;Okamoto et al, 1998;Olsson et al, 2011;Hiraga and Nakamura, 2016).…”
Section: Cancer Stem Cells Molecular Characterization Of Cancer Stem Cellsmentioning
confidence: 99%
“…The in vitro cytotoxicity analysis of MTX-EDA-PEG-EDA-HA NPs and free MTX against two cell lines with different levels of CD44 expression (MDA-MB-231 (very high) and MCF-7 (low)) [16,17] was conducted by MTT assay. The cells were cultured in RPMI 1640 media supplemented with 10% FBS and 100 lL of penicillin G/streptomycin mixture at 37 C in a humidified CO 2 incubator [18,19].…”
Section: Cytotoxicity Testmentioning
confidence: 99%